Extent of mobile phone technology use in marketing agricultural products in Ankpa L.G.A Kogi State, Nigeria - Ibrahim, M. K.; Adisa, R. S.; Ahmed, T. A.; Ebenehi, O. (ADAN JOURNAL OF AGRICULTURE, 2024)
This study examined the extent of use of mobile phone technology in marketing agricultural products in Ankpa Local Government Area of Kogi State. The study specifically described the socioeconomic characteristics of agricultural products marketers, extent of mobile phones usage in marketing agricultural product and the challenges associated with the use of mobile phones by the marketers. Two-stage random sampling technique was employed to select 120 agricultural products marketers and questionnaires were administered to them. The data obtained was analyzed using descriptive statistics and mean score from a Likert - type scale. Results from the study revealed that the marketers were dominated by (76.67%). Also, majority (70.8%) of the respondents were married, and had between male 1 to 10 years of experience in marketing. The results on extent of mobile phone usage revealed that it was used in obtaining prevailing market price ( = 3.91), getting updates on market situations ( = 3.78), level of demand of products ( = 3.25) to a great extent. The major challenges faced by the respondents in using the mobile device to market their products were lack of electricity (=3.75), network failure (=3.50), high tariff charges by operators (=3.38), and the high cost of mobile phones (=3.22). It is recommended that concerted efforts should be made by the government in stabilizing power supply in the country, so that the problem of power supply associated with the used of mobile phones in marketing of agricultural products can be resolved, and that the network service providers should make available toll-free lines where exchange of information related strictly to agriculture could be exchanged.